Specialized nursing terminology for the care of people with COVID-19 - Diego Dias de Araújo; Maria Naiane Rolim Nascimento; Écila Campos Mota; Maíra Marques Ribeiro; Renata Patricia Fonseca Gonçalves; Ricardo Otávio Maia Gusmão; Nuno Damácio de Carvalho Félix
ABSTRACT Objective: To create specialized nursing terminology for the care of people with COVID-19. Methods: Methodological study, carried out based on the identification of concepts related to the care of the person with the infection, present in the official guidelines of the Brazilian Ministry of Health; the concepts were validated by three specialist nurses; and a cross-mapping of the extracted concepts was done with CIPE® 2019 primitive concepts. Results: Out of 436 unique concepts, being 399 of these validated; of these, 70.9% were in the Classification and referred to the nursing care of people with COVID-19. In the Axis, the concepts related to Focus, Action, and Environment stood out. As for the non-validated concepts, 78.4% were not included in the 2019 version of CIPE®. Conclusion: We were able to structure a specialized CIPE® terminology, with the potential to generate nursing care indicators for people with COVID-19.